2021
DOI: 10.1111/birt.12537
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of women with low obstetric risk for cesarean or vaginal birth in Poland: Areas for intervention

Abstract: Background In Poland, the rate of cesarean birth (CB) is 43%, which is much higher than the European average of 27%. Optimizing the CB birth rate is of critical importance, especially among women with low‐risk pregnancies. However, the determinants of cesarean preference among low‐risk women in Poland have not been well explored. Methods This cross‐sectional study included 1011 pregnant women and aimed to identify associations between selected determinants of women's preferences for CB vs. vaginal birth (VB) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Based on research, fear of pain during VB is linked to asking for a CB. [22,23] The connection between helplessness (stress coping strategy) and estimation of greater pain during VB than CB obtained in our research, is a phenomenon that may lead students with these characteristics to prefer and recommend CB in their future practice.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Based on research, fear of pain during VB is linked to asking for a CB. [22,23] The connection between helplessness (stress coping strategy) and estimation of greater pain during VB than CB obtained in our research, is a phenomenon that may lead students with these characteristics to prefer and recommend CB in their future practice.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, the highest CB rates are reported in the regions of Poland where epidural access is the most limited. [23] In our study, we were interested in medical students' opinions, and at the same time, we wondered whether emotions were related to attitudes towards CB and VB. As our study showed, stress coping strategies seem to be related to the understanding of the childbirth process and the set of attitudes connected with it.…”
Section: Demographic Characteristics Of the Medical Studentsmentioning
confidence: 99%
“…Reports have identified a lack of pain alleviation during VB and birth-related pain fear as significant variables associated with elevated CS rates [ 4 , 18 , 31 ]. Moreover, in some students’ opinions, pain associated with vaginal delivery was a reason to opt for CS [ 27 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 9-35% of women experience severe FOC, which correlates with many possible complications [7,9]. It is well documented that PrA and FOC correlate with prolonged durations of active labor, the greater use of pain relief, higher rates of emergency cesarean sections (CSs), higher rates of cesarean sections without medical indications, the induction of labor, and other obstetric interventions [9][10][11][12][13][14][15][16][17]. It has also been proven that PrA is associated with negative personal birth experiences, adversely affects mother-child bonding, impedes effective breastfeeding, and may be a predisposing factor in the development of postpartum depression and even postpartum psychosis [3,5,6,18].…”
Section: Introductionmentioning
confidence: 99%
“…Polish perinatal care involves an exceptionally high rate of cesarean sections (47% in 2022) [13], and the reason for this phenomenon remains unknown. In addition, epidural availability in Poland is currently insufficient, and only 35-40% of women in labor have access to this procedure [14]. Interestingly, the highest CS rates are reported in the regions of Poland where epidural access is the most limited due to an insufficient number of anesthesiologists.…”
Section: Introductionmentioning
confidence: 99%